Assessment Of Knowledge And Attitude Among Mahsa Medical Students Towards HIV/AIDS - Aws Hashim Ali Al-Kadhim; Sarah Taha Yousif Al-Ani; Munandy Alagar; Lee Phon Yong; Gomalata Devadas; Chandrasekaran Selvaraj; Meram Azzani (Faculty of Medicine,Universiti Teknologi MARA, 2024)
Volume: 7 No: 1 (page: 36-47)